Anatomical Correction and Early Outcomes of One-step Ventral and Dorsal Proctoplasty in Girls with Low Anorectal Malformations - Vinit, Nicolas; Glenisson, Mathilde; Leroy, Justine; Sarnacki, Sabine; Crétolle, Célia; Beaudoin, Sylvie (European Journal of Pediatric Surgery, 2025)
Rectoperineal fistula (RPF) and rectovestibular fistula (RVF) are the most common forms of low anorectal malformations (ARMs) in girls, and lead to difficult stooling, thus demanding early surgical correction. This study's aim was to assess early outcomes associated with one-step ventral and dorsal proctoplasty in RPF/RVF.All female infants who consecutively underwent one-step proctoplasty for RPF/RVF at our institution (2012–2022) were retrospectively included. Reviewed data included: age at procedure, congenital anomalies, fistula location, preoperative symptoms, intraoperative findings, operative time, postoperative complications, and bowel functional outcome. Success of the technique, defined as spontaneous bowel movement at last follow-up without anal dilation, was assessed. Secondary outcomes included resolution of preoperative symptoms, and Krickenbeck score and fecal continence in girls older than 3 years at last follow-up. No preoperative bowel preparation was necessary.None of the 77 included girls (median age at surgery: 3.2 months (2.3–7.3)) had prior colostomy. In every case, intraoperative findings included: ventral defect of the external anal sphincter, and abnormal attachment of the bulbospongiosus muscles to the fistula and posterior ledge, thus justifying both ventral and dorsal reconstructions. The median operative time was 34 min (27–38), and the median hospital stay was 2 days (2–3). Limited ventral skin dehiscence was the most common postoperative complication (31%), with limited effect on clinical outcome (one secondary anal stricture). No child required secondary colostomy or revision anoplasty. One child underwent secondary pull-through due to persistent megarectum. Preoperative symptoms resolved in 98% of cases. After a median follow-up of 27.6 months (9.8–48.3), all girls had spontaneous bowel movement and 21% had grade-2 constipation. The technique was successful in 97% of cases (two anal strictures treated with dilations).RPF/RVF in female share abnormal anatomical characteristics. One-step ventral and dorsal proctoplasty allows precise anatomical correction of low ARM in girls.
Keywords: anorectal malformation; proctoplasty; terminal constipation; bulbospongiosus muscle; perineal body